Role of micF in the tolC-mediated regulation of OmpF, a major outer membrane protein of Escherichia coli K-12. - Misra, R (1987)
Mutation in the tolC locus greatly reduces normal synthesis of OmpF, a major porin protein of Escherichia coli K-12. Experiments that use ompF-ompC chimeric genes demonstrate that a tolC mutation exerts its effect at either the promoter or the amino-terminal end of the ompF gene. Direct analysis of ompF mRNA from tolC+ and tolC strains showed that the amount of ompF transcript in the latter was greatly reduced. We have also observed that, in addition to reducing the amount of OmpF, a tolC mutation increases the level of OmpC protein to a much greater extent than occurs in an OmpF mutant and also increases micF RNA synthesis as shown by increased beta-galactosidase synthesis in a micF-lacZ fusion strain. Based on these observations, we suggest that an increased expression of the micF gene in a tolC mutant results in the reduced expression of ompF and that a major effect of the tolC mutation may be to push the porin-regulating system to favor ompC and micF to a greater extent than under high-osmolarity conditions.